Digitalization of financial systems and cross-border integration: on the issue of creating a currency instrument for the BRICS countries - V. P. Akinina; D. A. Zakharova (Вестник Северо-Кавказского федерального университета)
Introduction. The development of digital technologies opens up new opportunities for increasing the efficiency, transparency and accessibility of financial services, and also promotes the deepening of economic cooperation between countries.The issue is particularly relevant for the BRICS countries, which demonstrate high rates of economic growth and are interested in developing mutually beneficial partnerships.Goal. The study of theoretical aspects of digitalization of financial systems and crossborder integration in the context of prospects for creating a currency instrument for the BRICS countries.Materials and methods. The study used the method of analyzing scientific articles, monographs and dissertations on the research topic, collecting and systematizing statistical data, comparing foreign experience in creating supranational currency instruments, the method of modeling and expert assessments. The information base of the study includes scientific articles and publications in scientific journals, dissertations, monographs on the topic of the study, Internet resources, and analytical reviews.Results and discussion. The experience of creating supranational currency instruments, their advantages and disadvantages were analyzed. The analysis showed that the BRICS countries demonstrate significant potential in developing financial cooperation, creating platforms and instruments for mutual settlements, but they face a number of structural problems and challenges. Comparison with the best foreign practices reveals significant potential to improve payment instruments, in particular, to create a blockchain foreign trade settlement system. Such efforts lay the foundation for an alternative financial paradigm, strengthening the position of BRICS in the global economic environment.Conclusion. The analysis of the current state of the financial systems of the BRICS countries, their level of digitalization and interaction in the financial sector allowed the authors to conclude that there is potential for the formation of an alternative financial system and strengthening the role of BRICS in the global economy.